Rancang Bangun Aplikasi Penilaian Kinerja Tenaga Kontrak Dinas Penididikan Kota Surabaya Dengan Metode Graphic Rating Scales - Permana, Dian Bagus Eka; Tjandrarini, A. B. Tjandrarini B.; Nurcahyawati, Vivine Nurcahyawati Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Dinas Pendidikan ( dispendik ) surabaya is implementing the element of local government in charge of teachers and contract workers in the city of Surabaya. The labor contract to extend the service life of each year. Extension of the term based on the results of the assessment carried out by energy performance contracts passed. But in reality the process of assessing the performance of contractors Dispendik Surabaya often not timely. The result is the value of power contracts late exit, labor contract renewal letter is given too late, and the payroll year-end book closing Dispendik Surabaya be too late. Based on the above problems, Dispendik Surabaya require application performance appraisal contract workers in accordance with the provisions of Dispendik Surabaya. Application performance assessment by Graphic Method of Rating Scales can help the problems experienced in the judging process this time. With the application of the assessment can be done anywhere and at any time and in accordance with the position designated by the Head of Public and Civil Service Rate the performance of this contract labor produces value contract staff in accordance with the provisions of Dispendik Surabaya. Use of Graphic Method of Rating Scales in the application can provide information on the results the best value of the contract staff who passed the performance assessment. Based on application testing, has shown the value of 85% stating that suits your needs and fit for use